Neural gain induced by startling acoustic stimuli is additive to preparatory activation - McInnes, Aaron; Corti, Emily; Tresilian, J.R.; Lipp, Ottmar; Marinovic, Welber (WILEY, 2020)
© 2019 Society for Psychophysiological Research